Philanthropy, Civil Society and Terrorism - Dharitri Dwivedy (Philanthropy, Civil Society and Terrorism, 2021)
This book examines the role of the state with regard to the regulation of the Non-Governmental Organizations (NGOs) in the context of their linkages to terrorism. Conventional counterterrorism approaches prefer law-enforcement means - strict regulation and monitoring and even clampdown - to prevent the abuse of NGOs by terrorists. However, as this research demonstrates, exploitation of the NGOs by the terrorists is not inherently structural and the NGOs and the state have strong compatibilities with the former complimenting several functions of the state – delivery of public goods such as human security, human rights and development - often more optimally than the state. Hence, a strict regulatory approach towards the working of NGOs could be counterproductive. Sporadic instances of abuse or misuse of NGOs generally and charities specifically by terrorists do not merit an overwhelming law enforcement response of a severity that would stifle the spirit of philanthropy and self-help in the society. To the extent that the NGO sector significantly contributes to peoples’ welfare, engage in conflict avoidance and conflict management initiatives and mitigate the consequences of conflicts, pandemics, environmental or natural disasters, it becomes a competent stakeholder and a partner to the state by its own right. Therefore, co-option of the NGO sector would supplement state’s efforts to deliver various public goods efficiently. Hence, the policies, procedures, and regulations concerning NGO governance should be such that the NGO sector can continue to be a partner to the state in development, supplementing the delivery of important public goods and not be used as fronts for terrorists.